2022
DOI: 10.3389/fpsyg.2022.803184
|View full text |Cite
|
Sign up to set email alerts
|

Social Value Orientation Moderated the Effect of Acute Stress on Individuals’ Prosocial Behaviors

Abstract: Acute stress is believed to lead to prosocial behaviors via a “tend-and-befriend” pattern of stress response. However, the results of the effect of acute stress on prosocial behavior are inconsistent. The current study explores the moderating effect of gender and social value orientation on the relationship between acute stress and individuals’ pure prosocial behaviors (i.e., pure prosociality and prosocial third-party punishment). Specifically, eighty-one participants were selected and underwent the Trier Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…Our study extends previous findings demonstrating the importance of individual differences in empathy (31), mentalising (33), and Social Value Orientation (34) in predicting prosocial responses under acute stress. However, it is not yet clear when acute stress accentuates or supresses existing prosocial tendencies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study extends previous findings demonstrating the importance of individual differences in empathy (31), mentalising (33), and Social Value Orientation (34) in predicting prosocial responses under acute stress. However, it is not yet clear when acute stress accentuates or supresses existing prosocial tendencies.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Speer et al (32) showed that acute stress can accentuate existing differences in dishonesty (cf. 33,34). Thus, our study also aimed to test whether individual differences in participants' trait prosocial tendencies, as measured by Social Value Orientation (SVO; 29), modulated the impact of acute stress on effortful prosocial behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Such use of deception is a common practice of previous studies (Blain et al, 2022; FeldmanHall et al, 2014; Leliveld et al, 2012; McAuliffe et al, 2015; Qu et al, 2018; Stallen et al, 2018; J. Yang et al, 2022; Ying et al, 2022). Since all players in the task were anonymous, no reputation concern was involved in this task.…”
Section: Methodsmentioning
confidence: 99%
“…Social value orientation refers to a personality trait that reflects stable individual differences. Exist when people weigh their own outcomes in social dilemmas and compare them to those of others [9]. The study by Ying, and colleagues studies the moderating role of gender and social value orientation on the relationship between acute stress and individuals' purely pro-social behaviour (i.e., purely pro-sociality and pro-social third-party punishment) Participants being randomly assigned to stress condition and control condition.…”
Section: Gender Differences Stress and Prosocial Behaviourmentioning
confidence: 99%
“…The result shows that acute psychological stress affects the frequency and amount of punishment in purely pro-social punishment and pro-social thirdparty punishment, i.e., donation and third-party punishment tasks in the dictator game. In addition, these effects varied according to participants' gender and social value orientations [9].…”
Section: Gender Differences Stress and Prosocial Behaviourmentioning
confidence: 99%